Konstruksi Konten Vlog Penerima Diamond Play Button Di Youtube Indonesia - Nunik Hariyani (Universitas Merdeka Madiun, 2020)
Abstractâ€” The existence of YouTube since 2005, is currently the second most popular social network in the world after Facebook. YouTube users in the world 1.9 billion. YouTube is used to share content and comments. This video-based social media is used to share videos and comment on one another. YouTube users in Indonesia have reached 50 million people. This research will look at how YouTube's Atta Halilintar and Ricis Official content constructions are recipients of the Diamond Play Button award, and how the creative strategy used by YouTuber in its video content. The results of this study are YouTube being the most active social platform used in Indonesia today. Youtube is used for identity and as a promotional media based on PPC (Pay Per Click) where every video that is deemed eligible in it contains Google Adsense ads. Youtube is a money field for many YouTubers in Indonesia with creative concepts according to popular culture.Â Keywordsâ€”: YouTube; Creative Strategy; Video Content; Construction.